International Development - Illusions and Realities - Black, Maggie (New Internationalist, 2015)
Part of the popular, reissued NoNonsense series from New International ist'Development' is often misunderstood and can embrace everything fro m building a large dam to planting trees. The idea can often mask conf usion, contradiction, deceit and corruption. This book is essential re ading for anyone wanting to know what development actually is. It cove rs all the key themes and critically suggests ways to bring the poor a nd marginalised into the process.